2023
DOI: 10.3390/separations10120596
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on Extraction, Separation, and Purification Methods of Plant Essential Oils

Weiwei Zhou,
Jun Li,
Xuefeng Wang
et al.

Abstract: Essential oils (EOs), also called liquid gold, are known for their wide range of applications and biological activities. The modern use of EOs has received increasing attention for more than 60 years. The precious EOs have been refined from plant raw materials using a variety of methods. Since the extraction, separation, and purification methods determine the type, quantity, and stereochemical structure of EO molecules as well as the final yield and quality of EOs, the selection of an appropriate method is cru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 118 publications
0
1
0
Order By: Relevance
“…The seed extract of M. oleifera from Iraq resulted in 41 bioactive compounds by GC-MS analysis, and Pentadecanoic acid 34.43% being the major one (AL-Obaidi et al 2021). GC-MS analyzed thirty-six phyto-compounds in a study carried out in Tunisia, Cis, 6-octadecenoic acid showed the highest peak area (70.68%) (Zhou et al 2023).…”
Section: Figure 1 Schematic Representation Of Phytochemical Analysis ...mentioning
confidence: 99%
“…The seed extract of M. oleifera from Iraq resulted in 41 bioactive compounds by GC-MS analysis, and Pentadecanoic acid 34.43% being the major one (AL-Obaidi et al 2021). GC-MS analyzed thirty-six phyto-compounds in a study carried out in Tunisia, Cis, 6-octadecenoic acid showed the highest peak area (70.68%) (Zhou et al 2023).…”
Section: Figure 1 Schematic Representation Of Phytochemical Analysis ...mentioning
confidence: 99%